2022
DOI: 10.56825/bufbu.2022.4133165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of season and stage of lactation on milk components in Purnathadi buffaloes

Abstract: The present study was designed to observe the effect of season and stage of lactation on milk components of Purnathadi buffaloes. Total 346 milk samples were collected, from three different seasons (winter, summer and rainy) and stage of lactation (early, mid and late) for the study. Overall milk fat, protein, lactose, solid not fat (SNF) and total solids (TS) were observed as 8.44±0.07, 3.99±0.02, 3.96±0.02, 8.78±0.04, and 17.23±0.08% respectively. There was significantly higher fat and total solids percent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Our results are consistent with this view, as glu levels reached maximum values when the load was 500 kg. The glu values observed in the present study are consistent with those in adult buffaloes previously reported by Mahardika et al [9], Mahardika et al [41], and Kuralkar et al [50]. In general, glu concentrations above reference values can be attributed to the activation of the hepatic processes of glycogenolysis and gluconeogenesis, which is a response to the energetic need to maintain muscle activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with this view, as glu levels reached maximum values when the load was 500 kg. The glu values observed in the present study are consistent with those in adult buffaloes previously reported by Mahardika et al [9], Mahardika et al [41], and Kuralkar et al [50]. In general, glu concentrations above reference values can be attributed to the activation of the hepatic processes of glycogenolysis and gluconeogenesis, which is a response to the energetic need to maintain muscle activity.…”
Section: Discussionsupporting
confidence: 92%
“…[ 41 ], and Kuralkar et al . [ 50 ]. In general, glu concentrations above reference values can be attributed to the activation of the hepatic processes of glycogenolysis and gluconeogenesis, which is a response to the energetic need to maintain muscle activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method offers a convenient assay of large numbers of samples with excellent precision. The practice of RIA in the measurement of hormones for veterinary clinical use has been extensively studied in India (Dadke et al, 2018;Roopali et al, 2020;Galdhar et al, 2021;Jayabhaye et al, 2021;Galdhar et al, 2022 andSalutgi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in thyroid hormone concentrations in response to Non-Thyroid Illness (NTIs) are well recognized in veterinary clinical practice ( 1 , 2 ). In severe NTIs, there is a decreased concentration of Triiodothyronine (TT 3 ) and Total thyroxine (TT 4 ).…”
Section: Introductionmentioning
confidence: 99%